Community-Based Health Education Improve Knowledge and Attitudes of COVID-19 Prevention - Emdat Suprayitno; Hidayat, Syaifurrahman; Mumpuningtias, Elyk Dwi; Dian Permatasari; Wardita, Yulia (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Corona Virus Disease-19 is becoming a pandemic. The easy-to-spread nature of the virus which requires good knowledge and good attitude in determining preventive measures to break Covid-19 transmission.Purpose: This study aimed to determine the effect of community-based health education on knowledge and attitudes of Covid-19 prevention.Methods: This is quantitative research with design of quasi-experimental. The sampling technique used was simple random sampling, the samples were 62 people divided into two groups. The intervention group that received the intervention of community-based health education and control group that received a Covid-19 leaflet.Results: The research result found that Mann Whitney U test score of knowledge between intervention and control group after the given intervention was p=0.004. Independent T test score of attitudes between intervention and control group after intervention was p=0.003. The Mann Whitney U test score of knowledge differences (?) between intervention group and the control group after intervention was p=0.002. Mann Whitney U test of attitudes differences (?) between intervention group and the control group after intervention was p=0.000.Conclusion: The research showed that respondents in the intervention group have better knowledge and better attitudes. The community-based health education method can be an alternative option to promote and prevent the spread of Covid-19 infection